2022
DOI: 10.3389/fnagi.2022.910886
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on electroencephalogram measures of anesthesia hypnosis: A comparison of BIS, Alpha Power, Lempel-Ziv complexity and permutation entropy during propofol induction

Abstract: BackgroundImproving anesthesia administration for elderly population is of particular importance because they undergo considerably more surgical procedures and are at the most risk of suffering from anesthesia-related complications. Intraoperative brain monitors electroencephalogram (EEG) have proved useful in the general population, however, in elderly subjects this is contentious. Probably because these monitors do not account for the natural differences in EEG signals between young and older patients. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…In addition, many studies have indicated that traditional EEG-based Lempel–Ziv complexity is decreased after anesthesia. 25–27 However, in our study, the Lempel–Ziv complexity based on microstate sequences showed the opposite trend. From the statistical analysis of the occurrence and duration measures of microstates in table 1, we found that the duration of most microstates is shorter compared to the awake state.…”
Section: Discussioncontrasting
confidence: 78%
“…In addition, many studies have indicated that traditional EEG-based Lempel–Ziv complexity is decreased after anesthesia. 25–27 However, in our study, the Lempel–Ziv complexity based on microstate sequences showed the opposite trend. From the statistical analysis of the occurrence and duration measures of microstates in table 1, we found that the duration of most microstates is shorter compared to the awake state.…”
Section: Discussioncontrasting
confidence: 78%
“…The diversity of continuous brain activity constitutes a sensitive and robust neuronal marker of the global states of consciousness [12,13,14,15,16,17,18]. Accordingly, it has been proposed that these diversity measures are closely related with conscious experience, specifically with its richness, vividness, and temporal variability [23,24,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Lempel-Ziv diversity of continuous brain signals has also been shown to successfully predict global states of consciousness. Specifically, the diversity of continuous brain signals decreases during NREM sleep [12,13], propofolinduced anesthesia [14,15,16], and in patients suffering from disorders of consciousness [17].…”
Section: Introductionmentioning
confidence: 99%
“…For GABAergic anesthetics (i.e. propofol and sevoflurane), the EEG changes from a wide band to a regular oscillation after LOC, and PE measures decrease in complexity after anesthesia [46]. However, (S)ketamine promotes abnormal excitement and high frequency power in EEG after induction.…”
Section: Permutation Entropy (Pe) Analysismentioning
confidence: 99%